IN VITRO ANTI-INFLAMMATORY ACTIVITY TEST OF TINOCRISPOSIDE AND FREEZE-DRIED AQUEOUS EXTRACT OF TINOSPORA CRISPA STEMS ON HUMAN RED BLOOD CELL BY INCREASING MEMBRANE STABILITY EXPERIMENT - ADEK ZAMRUD ADNAN; FITHRIANI ARMIN; IKHWAN RESMALA SUDJI; MEDIOLA DWI NOVIDA; DEWI IMELDA ROESMA; HANA AFIFAH ALI; ANNISA FAUZANA (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: This study was aimed to evaluate the anti-inflammatory effect of isolated tinocrisposide and freeze-dried aqueous extract of Tinospora crispa stems on human red blood cell (HRBC) by increasing membrane stability in vitro models. Methods: Anti-inflammatory effect of tinocrisposide and FDAETCS was evaluated by in vitro HRBC membrane stabilization method. The study was separated into two steps which were a hemolytic and a membrane stabilization experiment. The hemoglobin that was released throughout the damaged erythrocytes membrane was then quantified at the wavelength of (λ) 560 nm. Results: The hemoglobin in the HBRC supernatant that treated with tinocrisposide at concentration of 100, 200, 400, 600, 800, and 1000 μg/ml showed an absorbance at λ 560 nm of 0.060, 0.061, 0.071, 0.072, 0.075, and 0.0793, respectively, and the calculated hemolysis percentage was 0.032, 0.097, 1.203, 1.236, 1.641, and 2.079%, respectively. We found a linear correlation between concentration and hemolytic activity of tinocrisposide, with regression equation, y=0.0023x−0.1312 (r=0.929). Meanwhile, the HBRC supernatant that treated with FDAETCS at concentration of 100, 200, 400, 600, and 800 μg/ml showed an absorbance at λ 560 nm of 0.063, 0.064, 0.066, 0.067, and 0.077, respectively, and revealed the hemolytic percentage of 0.347, 0.473, 0.693, 0.992, and 1.896%, respectively. It also gave a linear correlation between FDAETCS concentration and hemolytic activity percentage, with regression equation, y=0.002x+0.0222 (r=0.895). Moreover, in HRBC membrane stability experiment, tinocrisposide concentration of 100, 200, 400, 800, and 1000 μg/ml gave absorbance at λ 560 nm of 0.818, 0.808, 0.798, 0.789, 0.773, and 0.761, respectively, and calculated HRBC membrane stabilization activity as much as 5.437, 6.533, 7.707, 8.748, 10.597, and 12.100%, respectively. Meanwhile, the positive control ibuprofen 25 μg/ml only exerted the membrane stability of 5.620%. It was found a linear correlation between tinocrisposide concentration and membrane stability percentage, with the regression equation, y=0.0072x+4.8312 (r=0.9932). Treated FDAETCS in the concentration of 100, 200, 400, and 800 μg/ml gave the absorbance at λ 560 nm of 0.802, 794, 0.777, 0.791, and 0.792, with stability membrane percentage of 7.283, 8.208, 10.944, 8.555, and 8.401%, respectively. It can be seen that the FDAETCS concentrations and its hemolytic percentage showed a parabolic relationship, which gave a maximum at a concentration of the extract of 400 mg/ml with membrane stabilizing of 10.944%. Conclusion: It can be concluded that tinocrisposide and FDAETCS have an anti-inflammatory activity by increase the membrane stability of lysosome cell that has equal physiological properties with erythrocytes membrane cell and it has no hemolytic activity.